Contemporary Ashkenazic Hebrew: The Grammatical Profile of an Overlooked Twenty-First-Century Variety - Kahn, Lily (Journal of Semitic studies, 2022)
Ashkenazic Hebrew is a unique language variety with a centuries-long history of written use among Central and Eastern European Jews. It has distinct phonological and grammatical features attested in texts composed by Ashkenazic Jews (e.g. adherents of the Hasidic and Maskilic movements) in Europe prior to the twentieth century. While Ashkenazic Hebrew is commonly believed to have been replaced by Israeli Hebrew in the twentieth century, this traditional written variety of the language actually continues to thrive in contemporary Diaspora Haredi (strictly Orthodox) communities, chiefly the Hasidic centres of New York, London, Montreal and Antwerp. This fascinating and understudied form of Hebrew is used widely and productively in the composition of a rich variety of original documents for a Hasidic audience (about e.g. Covid transmission, United States educational stipulations, Zoom schooling, lockdown rules, etc.). In this article we demonstrate that contemporary Ashkenazic Hebrew has many shared orthographic, phonological, grammatical and lexical features with its Eastern European antecedent. These include: orthography of loanwords based on Yiddish conventions (e.g. חולי הקאראנא xóylay ha-koróna ‘those ill with coronavirus’); morphology of plural loan nouns (בקאלידזשעס be-kóleǧes‘in colleges’, הפראגראמע״ן haprográmen ‘the programmes’); retention of the definite article with inseparable prepositions (בהשכונה be-ha-šxíne‘in the neighbourhood’);